Analisis Manajemen Risiko Pengelolaan Limbah Medis dalam Upaya Pencegahan dan Pengendalian Covid-19 di RS MMC Jakarta - Sarah Dani Agnesia Situmorang (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Hospitals are medical services that produce medical waste. The increasing number of positive cases of Covid-19 has resulted in an increase in the amount of medical waste. An assessment of the risks caused by the hazards is required. This study aims to analyze the risk management of medical waste in efforts to prevent and control Covid-19 at the MMC Jakarta Hospital. Using qualitative methods. Located at the MMC Hospital Jakarta in May-June 2022. Primary data collection comes from observations of waste management. Secondary data obtained from graphic documents. Risk identification was carried out from several problems by conducting interviews with the hospital. After that, an analysis is carried out based on the identification of the problem. MMC Hospital medical waste is treated in accordance with the designated waste designation based on applicable regulations. There are adequate policies and SOPs, human resources, funds, facilities and infrastructure. Sorting has been carried out between domestic waste and medical waste, with the exception of the Covid-19 treatment room. But still found disaggregation that is not appropriate. The volume of waste generated by the MMC Hospital from 2020-2021 has increased by 21.79% resulting in a 5x increase in spending. The regulations in force have not been implemented properly. Hospitals should increase monitoring and evaluation efforts in all aspects of managing Covid-19 medical solid waste. Conclusion There is a risk of increasing the volume of waste and increasing expenditure of funds in waste management. Research suggestions are to comply with the policies that have been made, adjust the budget based on needs evaluation, carry out guidance and supervision as evaluation material, conduct education and training related to waste management, pay attention to each component so that it is in line with hospital sanitation goals.